Organizational activity on hospital management - Baіevа, Olena; Baiev, Vadim (My University, 2021)
The function of management is aimed at building an organization and forming a system of relations in it is called "organization". Organization - a type of management activity aimed at forming a management structure of the organization, establishing a system of connections and relationships, which allows you to work effectively to achieve goals. The organization is a management function within which grouping and coordination of works, types of activity and resources for achievement of the set purposes is carried out. The implementation of the function of the organization is carried out in the process of organizational activities. Organizational activity is a process by which the manager eliminates uncertainty, forms the division of powers, responsibilities of management and production staff, in order to form effective joint activities.

Функція менеджменту спрямована на побудову. Організація і формування в ній системи відносин називається «організацією». Організація - вид управлінської діяльності, спрямований на формування менеджменту структура організації, встановлення системи зв'язків і відносин, що дозволяє ефективно працювати для досягнення цілей. Організація а Функція управління, в рамках якої здійснюється групування та координація робіт, види діяльність і ресурси для досягнення поставлених цілей. The Реалізація функції організації здійснюється в процесі організаційна діяльність. Організаційна діяльність — це процес, за допомогою якого менеджер усуває невизначеність, формує розподіл повноважень, відповідальності керівництва та виробничого персоналу, з метою формування ефективної спільної діяльності.
Keywords: management; organizational activity; provision of medical care; кафедра туристичного та готельного бізнесу; менеджмент; організаційна діяльність; надання медичної допомоги